Theoretical calculation of the structure of a polarizable-ionic fluid - Gray-Weale, A; Madden, P (2003)
Much theory of the structures of fluids depends on the assumption of pair-additive forces between the particles. Simulations and experiments have shown that many molten salts, molecular fluids and other systems have structures that depend sensitively on polarization of their electron clouds, or on other internal distortions. In such cases, the forces are not pair additive and the theoretical calculation of structure, expressed as a radial distribution function, g(r), is not possible using the ordinary methods. Part of the problem is that the internal structure is quantum mechanical. A theoretical method for the calculation of the structure of a fluid of polarizable particles is presented here, in a form that may be applied to any one of many structure theories in common use. The method is inspired by work on the simulation of polarizable fluids. It is applied to a simple model of a molten salt with polarizable ions. The theory is applicable to particles carrying any combination of induced electrical multipole moments, along with charges and permanent moments.